Cultural Barrier in the Regeneration Process of Islamic Political Party in Indonesia - Nastain, Muhamad; Abdullah, Irwan; Qodir, Zuly; Jubba, Hasse; Cipto, Bambang (SCAD Independent, 2024)
This research aims to describe the cultural barriers of the National Awakening Party (Partai Kebangkitan Bangsa or PKB) in promoting its members as candidates in direct presidential and vice-presidential elections. In the four general elections from 2004 to 2019, PKB failed to place its members as candidates. This condition is presumed to be due to cultural barriers embedded within the party’s internal dynamics and the cadre system. The research method employed in this study combined qualitative descriptive approaches by integrating literature studies with Focus Group Discussions (FGD) involving seven (7) competent informants comprising three media editors, two academics, one activist, and one politician. The data obtained from the FGD is the primary guide to trace document data. The data presentation involves triangulation of FGD data, document data, and field observation results. The data findings revealed three main pieces of evidence for cultural barriers: first, egocentrism of leaders and personal dependence, which refers to the positions of Kyai and Islamic Boarding Schools (pesantren) in the PKB cadre system; second, obedience that erases critical thinking, and third, the presence of the “green blood” identity, which holds privileges in the PKB’s cadre ship system. These three cultural barriers are not unique to PKB but are shared by most Islamic political parties in Indonesia.